Implications of Heart Failure Treatment on Atrial Fibrillation Onset: A Retrospective Study - Loredana Suhov; Adrian Apostol; Larissa Dăniluc; Lina Haj Ali; Oana Elena Sandu; Carina Bogdan; Minodora Andor (Medicina)
Background and Objectives: Atrial fibrillation (AF) is one of the most common supraventricular arrhythmias in the adult population worldwide and it is frequently associated with heart failure (HF). The coexistence of these conditions increases morbidity, mortality and reduces quality of life in these patients. Therefore, it is important to delay the onset of AF in HF patients in order to avoid complications. The study aims to assess whether HF treatment influences AF onset. Materials and Methods: This retrospective observational study included 260 patients, 144 patients with heart failure treated with sodium–glucose cotransporter 2 inhibitors (SGLT2i) and 116 patients with heart failure without SGLT2i treatment (control group) hospitalized at least twice in the Cardiology Department of the “Pius Brinzeu” Emergency County Hospital between 2022 and 2024. Results: Treatment with SGLT2i was associated with a lower prevalence of atrial fibrillation in patients with heart failure. Conclusions: The study highlights the cardiovascular benefits of SGLT2 inhibitors and suggests a potential effect on the onset of AF in heart failure patients.